The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jfpp.13400
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antifungal effects of thyme essential oil and Lactobacillus plantarum cell-free supernatant against Penicillium spp. and in situ effects

Abstract: This study evaluates the synergistic antifungal effects between thyme essential oils and Lactobacillus plantarum cell-free supernatant (LCFS) against Penicillium spp. and in situ antifungal activity in rice grains. Thyme essential oil and LCFS showed remarkable antifungal activities against Penicil- Practical applicationsEssential oils are used as preservative in food industry and high concentration of essential oil is associated with negative organoleptic characteristics. This study presented a novel approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Similar results were previously reported by various studies indicating that addition of EOs decreased the tensile strength of CS films and CS‐cassava starch composite films (Pelissari et al, ; Sriwattanachai et al, ). Sánchez‐Gonzáles et al () reported that the tensile strength of CS film decreased after incorporation of bergamot EOs.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were previously reported by various studies indicating that addition of EOs decreased the tensile strength of CS films and CS‐cassava starch composite films (Pelissari et al, ; Sriwattanachai et al, ). Sánchez‐Gonzáles et al () reported that the tensile strength of CS film decreased after incorporation of bergamot EOs.…”
Section: Resultssupporting
confidence: 91%
“…However, the combined effect of EOs and CS indicated higher intensity of antifungal response that was clearly evident from the microscopic examination. Similar results were reported by Sriwattanachai et al () who studied the effect of combined mixture of thyme EOs and Lactobacillus cell‐free supernatant on Penicillium spp. hyphae and chitin degradation in fungal cell wall.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…During processing food and personal hygienic conditions can prevent several foodborne diseases (Chanseyha et al, ). Several hygiene practices such as poor environmental and personal hygiene, improper cooking and preparation, insufficient storage of drinks and food are known to compromise the safety of food (Sriwattanachai, Sadiq & Anal, ).…”
Section: Introductionmentioning
confidence: 99%